Inside the campaign finance battle : court testimony on the new reforms - Corrado, Anthony, 1957-; Potter, Trevor; Mann, Thomas E. (Washington, D.C. : Brookings Institution Press, 2003)
The work examines the legal challenge to the new Bipartisan Campaign Finance Reform Act (BCRA) which is in federal court. It contains edited selections of reports filed by scholars and practitioners on both sides of the legal debate over the new campaign finance law.
Cover; Title Page; Contents; Editors' Note: An Explanation of This Volume; Introduction; Analyses of Academic Experts; Politicians and Party Officials; Scholarly Analyses; Views of the Advocates: Parties, Organized Groups, and Political Consultants; Evidence from Public Opinion Research; Donor Perspectives; Officeholder Prespectives; Party Chair Perspectives.
Includes bibliographical references.
Print version record.
JSTOR
Keywords: Campaign funds -- Law and legislation -- United States; Campaign funds -- United States; LAW -- Constitutional; LAW -- Public; POLITICAL SCIENCE -- Political Process -- Elections; Campaign funds; Campaign funds -- Law and legislation; United States